GEOELECTRIC INVESTIGATION USING VERTICAL ELECTRIC SOUNDING METHOD TO DETERMINE UNDERGROUND WATER AQUIFERS IN THE CASE OF PUDAK AND ITS SURROUNDING AREAS - Rohima Sera Afifah (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2023)
Resistivity is a determinant of the type of rock and the electrical properties of the rock or water-carrying layer. Primary data is the main source of data for the investigation of the subsurface with the Vertical Electric Sounding (VES) method. The purpose of the study is to determine the resistivity of subsurface geological conditions to detect aquifer and reservoir lithology types designed as planned wells. The data of geoelectric investigation point was carried out on as many as 10 (ten) points and produced in the form of (1) Claystone: resistivity of 1.4-6.4 Wm and thickness of 4-4.6 meters, (2) Sandstone: resistivity of 7.5-40 Wm and thickness of 0.2-55 meters, (3) Breccia: resistivity of 45-1088 Wm and thickness of 0.5-33.2 meters. For a depth aquifer of 5.8-68 meters and resistivity of 12.40-23.60 Wm with a shallow well condition around reaching a depth of 15-19 meters and freshwater results are obtained.